Implementation of Virtual Reality (VR) Technology in the North Sumatra Museum Virtual Tour to Enhance Visitor Interactivity - Feri Rinto Bashari; Ruly Dwi Arista; Randi Rian Putra (Sean Institute, 2026)
Museums, as cultural preservation institutions, play a strategic role in conveying historical values to the public; however, they face challenges related to access, distance, and the time spent by visitors. The purpose of this research is to create interactive and easily accessible digital media for teaching and promoting the North Sumatra State Museum thru a 360° Virtual Tour. This research uses the Multimedia Development Life Cycle (MDLC) method, which includes the phases of concept, design, material gathering, creation, testing, and distribution. The 3DVista Virtual Tour application is used to develop virtual tours that utilize 360° panoramic photos, videos, audio, and interactive hotspots to visually and informatively convey information about museum collections. The research results show that the virtual tour created can make the space of the North Sumatra State Museum an immersive and interactive experience. The results of system testing using the Black Box Testing method show that all important system features, including inter-room navigation, information hotspots, panorama control, and multimedia display, can operate well and stably. Therefore, this virtual tour is expected to serve as an alternative way to learn history, support cultural preservation, and increase public interest, especially among young people, in the North Sumatra State Museum.